Fraud: A Review and Research Agenda - PAN, Gary (Institutional Knowledge at Singapore Management University, 2011)
Corporate scandals such as Enron, Tyco, WorldCom and Adelphia have drawn significant attention to the occurrence of fraud. This has implications for public interest as the prevalence and consequences of fraud may affect the shareholders, creditors and the public’s confidence in the financial system. Much research has been published on various aspect of fraud. In this paper, we selected fraud articles published in accounting and management journals between 1996 and 2010 based on selected search phrases. We identified a total of 56 articles and perform content analysis on the fraud phenomenon in the articles, classified them into a number of fraud topics and eventually developed three fraud themes that encapsulate the fraud literature in the selected articles. The fraud themes from our content analysis are (1) Factors, Motivations and Antecedents of Fraud, (2) Auditor’s Role in Fraud Detection and Prevention, and (3) Information Technology Fraud. In addition, we also noted how the research was done and what we have learned from the research that could help researchers better understand fraud. The opportunities identified from this review may allow researchers to explore important research agenda.